Introduction to Theological Libraries (The Theological Librarian's Handbook, 2020)
The Theological Librarian's Handbook is a multi-volume guide to the practice of theological librarianship intended for library staff who do not possess professional training in the field of library and information science. It offers perspectives and advice from leading experts in the field and best practices from theological libraries all over the world.